Entanglement with three oscillators - Ahmad Zukarnain, Zuriati; Konstadopoulou, A.; Vourdas, A. (2005)
A system consist of three oscillators A, B and C are considered. It is assumed that the oscillators B and C are interacting with each other where as the oscillators A and C are entangled despite of the fact that they have never interacted with each other.